Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbasis Joyful Learning (Inter-joy) terhadap Keterampilan Proses Sains Siswa Kelas X SMA Negeri 2 Surakarta Tahun Pelajaran 2012/2013 - Alfian Chrisna Aji; Slamet Santosa; Riezky Maya Probosari (BIO-PEDAGOGI, 2014)
The aim of this research is to ascertain the influence of guided inquiry based joyful learning (interjoy) learning models toward science process skills of X grade students at SMA Negeri 2 Surakarta in academic year 2012/2013. This research was quasi experiment research which used posttest only nonequivalent control group design. This research applied guided inquiry based joyful learning (interjoy) learning models in experimental group and direct instruction learning models in control group.  The population of this research was all of X grade students at SMA Negeri 2 Surakarta in academic year 2012/2013.   Sampling techniques used cluster sampling that choosed X.10 as experiment group and X.8 as control group. Data was collected using KPS test, observation sheet, and document.  The hypotheses analyzed by t-test. This research concluded that application of guided inquiry based joyful learning (interjoy) learning models has real influential toward science process skills of X grade students at SMA Negeri 2 Surakarta. Key Words: guided inquiry based joyful learning (interjoy) learning models, science process skills